Vandetanib as a prospective anti-inflammatory and anti-contractile agent in asthma - Zeng, Xiaoyue; Xue, Lu; Li, Wei; Zhao, Ping; Chen, Weiwei; Wang, Wenyi; Shen, Jinhua (Frontiers in Pharmacology, 2024)
Background: Vandetanib is a small-molecule tyrosine kinase inhibitor. It exerts its therapeutic effects primarily in a range of lung cancers by inhibiting the vascular endothelial growth factor receptor 2. However, it remains unclear whether vandetanib has therapeutic benefits in other lung diseases, particularly asthma. The present study investigated the pioneering use of vandetanib in the treatment of asthma. Methods:In vivo experiments including establishment of an asthma model, measurement of airway resistance measurement and histological analysis were used primarily to confirm the anticontractile and anti-inflammatory effects of vandetanib, while in vitro experiments, including measurement of muscle tension and whole-cell patch-clamp recording, were used to explore the underlying molecular mechanism. Results:In vivo experiments in an asthmatic mouse model showed that vandetanib could significantly alleviate systemic inflammation and a range of airway pathological changes including hypersensitivity, hypersecretion and remodeling. Subsequent in vitro experiments showed that vandetanib was able to relax the precontracted rings of the mouse trachea via calcium mobilization which was regulated by specific ion channels including VDLCC, NSCC, NCX and K+ channels. Conclusions: Taken together, our study demonstrated that vandetanib has both anticontractile and anti-inflammatory properties in the treatment of asthma, which also suggests the feasibility of using vandetanib in the treatment of asthma by reducing abnormal airway contraction and systemic inflammation.